Construction and Exixtence of Islamic Educational Management Science - Nur Efendi; Nikmah, Laily Faridhatun; Akhyak Akhyak (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
The purpose of this study is to determine the construction and existence of Islamic educational management science. The research conducted is descriptive in nature where researchers collect words not in the form of a series of numbers for this study which in essence these words can provide a description or present existing problems and problem solving. The data analysis used is by analyzing the content, where the analysis emphasizes more on describing the contents of various existing propositions that are born from various theories and previous analyses conducted by other researchers. The results of the study indicate that the construction of science or the order of science is certainly related to several understandings about how someone seeks knowledge. The construction of the Islamic education system refers to the process of planning, organizing, and implementing various components and strategies of education based on the principles and values of Islamic teachings. The existence of Islamic Education Management shows that Islamic Education Management really exists and its existence is recognized in real terms by society. Existence Islamic educational management science focuses on governance actions that are considered not yet fully implemented by Islamic educational institutions, for example the concept of transparency and integrity. Theoretically, the discussion can be shifted to Islamic education science or to Islamic studies rather than directly to holy verses that can be dogmatic